To solve for \( d \) in the equation
\[ d - 8 = 3, \]
you can add 8 to both sides:
\[ d - 8 + 8 = 3 + 8. \]
This simplifies to:
\[ d = 11. \]
So, the solution is
\[ d = 11. \]
d − 8 = 3
d =
11 answers
To solve for \( d \) in the equation
\[ d - 8 = 3, \]
you can add 8 to both sides:
\[ d - 8 + 8 = 3 + 8. \]
This simplifies to:
\[ d = 11. \]
So, the solution is
\[ d = 11. \]
To solve for \( t \) in the equation
\[ 4t = 16, \]
you can divide both sides by 4:
\[ t = \frac{16}{4}. \]
This simplifies to:
\[ t = 4. \]
So, the solution is
\[ t = 4. \]
To solve for \( b \) in the equation
\[ \frac{b}{8} = 3, \]
you can multiply both sides by 8:
\[ b = 3 \times 8. \]
This simplifies to:
\[ b = 24. \]
So, the solution is
\[ b = 24. \]
To solve for \( z \) in the equation
\[ z + 2 = 99, \]
you can subtract 2 from both sides:
\[ z = 99 - 2. \]
This simplifies to:
\[ z = 97. \]
So, the solution is
\[ z = 97. \]
To solve for \( b \) in the equation
\[ b - 3 = 55, \]
you can add 3 to both sides:
\[ b = 55 + 3. \]
This simplifies to:
\[ b = 58. \]
So, the solution is
\[ b = 58. \]
To solve for \( h \) in the equation
\[ \frac{h}{6} = 9, \]
you can multiply both sides by 6:
\[ h = 9 \times 6. \]
This simplifies to:
\[ h = 54. \]
So, the solution is
\[ h = 54. \]